To be, or not to be in formalization: the relationship between HR practices and work engagement in the aviation industry - Koc, Emine Nihan; Bozkurt, Serdar; Varinlioglu, Selin Karaca (EMERALD GROUP PUBLISHING LTD, 2024)
PurposeThis study aims to examine the moderating role of formalization in the relationship between human resources (HR) practices and work engagement (WE) in aviation industry employees. The research revealed the moderator role of formalization, which is still one of the most critical components for aviation industry workers.Design/methodology/approachIn the study, the authors used the survey method. In this explanatory and cross-sectional study, the authors examined a data set collected from aviation industry employees (n = 226) in Turkey using the partial least squares (PLS) method and tried to moderate the formalization. The authors analyzed the moderator role of formalization in the relationship between HR practices and WE with SmartPLS 3.0 and HAYES Process Macro.FindingsThe results of the study explain the effect of HR practices on WE in the context of social exchange theory through formalization. Findings show that formalization is an essential factor in HR practices' resulting in higher WE.Research limitations/implicationsThe study is cross-sectional. Research participants participated in the study voluntarily. This situation, in turn, may lead to a social desirability bias in participants' self-reported responses. To avoid this, the authors have prepared a standardized measurement tool. Again, since the authors do not request the names and institutions of the participants, confidentiality and anonymity are provided.Practical implicationsResearch findings offer implications for companies and employees in developing economies, especially in the aviation sector. It refers to the necessity for companies aiming for a sustainable strategic position in the competitive aviation sector to attach importance to HR practices that will enable them to see their employees as a competitive advantage. In addition, the results emphasize the need for aviation industry companies to adopt an approach that considers both practices that can increase WE and formalization procedures that can affect employee behavior.Originality/valueThis research provides a comprehensive understanding to examine the interrelationships between HR, formalization and WE in the context of the mechanism of social change in the context of aviation industry workers. To the best of the authors' knowledge, no other researcher has holistically addressed these links in general, particularly in a developing country. The findings significantly enrich the literature on HR practices and WE, particularly in the context of a developing country.
Keywords: Human resource practices; Work engagement; Formalization; Aviation industry; HUMAN-RESOURCE MANAGEMENT; EMPLOYEE ENGAGEMENT; JOB-PERFORMANCE; MEDIATING ROLE; COMMITMENT; Engineering